Extrinsic and Local Glutamatergic Inputs of the Rat Hippocampal CA1 Area Differentially Innervate Pyramidal Cells and Interneurons - Takács, Virág T. (Hippocampus, 2011)
The two main glutamatergic pathways to the CA1 area, the Schaffer collateral/commissural input and the entorhinal fibers, as well as the local axons of CA1 pyramidal cells innervate both pyramidal cells and interneurons. To determine whether these inputs differ in their weights of activating GABAergic circuits, we have studied the relative proportion of pyramidal cells and interneurons among their postsynaptic targets in serial electron microscopic sections. Local axons of CA1 pyramidal cells, intracellularly labeled in vitro or in vivo, innervated a relatively high proportion of interneuronal postsynaptic targets (65.9 and 53.8%, in vitro and in vivo, respectively) in stratum (str.) oriens and alveus. In contrast, axons of in vitro labeled CA3 pyramidal cells in str. oriens and str. radiatum of the CA1 area made synaptic junctions predominantly with pyramidal cell spines (92.9%). The postsynaptic targets of anterogradely labeled medial entorhinal cortical boutons in CA1 str. lacunosum-moleculare were primarily pyramidal neuron dendritic spines and shafts (90.8%). The alvear group of the entorhinal afferents, traversing str. oriens, str. pyramidale, and str. radiatum showed a higher preference for innervating GABAergic cells (21.3%), particularly in str. oriens/alveus. These data demonstrate that different glutamatergic pathways innervate CA1 GABAergic cells to different extents. The results suggest that the numerically smaller CA1 local axonal inputs together with the alvear part of the entorhinal input preferentially act on GABAergic interneurons in contrast to the CA3, or the entorhinal input in str. lacunosum-moleculare. The results highlight differences in the postsynaptic target selection of the feed-forward versus recurrent glutamatergic inputs to the CA1 and CA3 areas.